DECLINE AND GROWTH FACTORS OF CREATIVE ACTIVITY OF KAZAKHSTAN COMPOSERS IN THE 1990-2000-IES - Raimkulova Aktoty (Scientific Journal of Pedagogy and Economics, 2020)
Based on objective data (the number of works written in major genres), I reveal a wave of decline and growth in the creative activity of Kazakhstan composers, which spanned two decades between 1990-ies and 2010-s. The article is devoted to an attempt to identify the external and internal causes of such statistics. The influence of the historical situation and the transformations of the cultural and ideological plan on musical creativity is analyzed. In my opinion,external factors affecting the creative activity of Kazakhstan composers are political changes and the ideological transformations associated with them, economic downturns and ups, as well as a system of intercultural interaction that is naturally transforming in the global world. A very indicative situation in the field of musical theater, which can be extrapolated to other genre spheres. It demonstrates a decline throughout the second half of the 1980s until the early 2000s. Among the factors that influenced the growth of creative activity in the late 1990s and early 2000s, state programs for the preservation of cultural heritage, new music festivals Nauryz-21, new technical capabilities (the emergence of modern recording equipment and computers, informatization) should be mentioned, expanding the scope of international and intercultural contacts. One of the most noticeable results of the activation of composer creativity was the formation of Kazakhstan polystylistics, which is characterized by a multi-vector combination of styles not only from different eras, but also from different musical and cultural traditions.